2016
DOI: 10.1126/science.aaf2144
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of protein phosphorylation across 18 fungal species

Abstract: Living organisms have evolved protein phosphorylation, a rapid and versatile mechanism that drives signaling and regulates protein function. We report the phosphoproteomes of 18 fungal species and a phylogenetic-based approach to study phosphosite evolution. We observe rapid divergence, with only a small fraction of phosphosites conserved over hundreds of millions of years. Relative to recently acquired phosphosites, ancient sites are enriched at protein interfaces and are more likely to be functionally import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(117 citation statements)
references
References 56 publications
3
114
0
Order By: Relevance
“…As an illustration of this, recent benchmarking on a large blind subset of the recently released SKEMPI 2.0 (487 mutations in 56 complexes), which none of the predictors had previously seen, showed that iSEE, FoldX, mCSM, and BindProfX did not perform as well as on the training sets they originally used with PCC values all below 0.4. Even so, we have seen some promising contributions of such predictors to practical problems, for example, References .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an illustration of this, recent benchmarking on a large blind subset of the recently released SKEMPI 2.0 (487 mutations in 56 complexes), which none of the predictors had previously seen, showed that iSEE, FoldX, mCSM, and BindProfX did not perform as well as on the training sets they originally used with PCC values all below 0.4. Even so, we have seen some promising contributions of such predictors to practical problems, for example, References .…”
Section: Discussionmentioning
confidence: 99%
“…From 2001, CAPRI has been playing a central role in stimulating the progress of docking algorithms and scoring functions as described in literature. 15,[101][102][103][104][105][106][107][108] In the 5th edition, CAPRI was extended to assess the methods to predict the impact of mutations for two designed influenza hemagglutinin binders based on yeast display enrichment data obtained using deep sequencing. 15,40,104 This assessment reported severe difficulties of docking scoring functions for predicting the impact of mutations on PPIs.…”
Section: Blind Challenges As Catalysts Of Developmentmentioning
confidence: 99%
“…Our own literature mining revealed (at that time) that the phosphoproteomic data available for fungi other than S. cerevisiae were rather limited, although very recently a comparative phosphoproteomic analysis has been performed in 18 fungi (Studer et al 2016). The only other closely related ascomycete for which sufficient phosphoproteomic data were available to allow meaningful comparative analyses was C. albicans , with two datasets comprising 9438 nonredundant p-sites.…”
Section: Resultsmentioning
confidence: 99%
“…Looking for phosphosites, where phosphate groups are added or removed, the mass spectrometry data highlights specific phosphosites that enjoy high degree of conservation; for example, at protein interfaces necessary for protein-protein interactions. 1 Subsequent assessment of the extent of binding affinity between kinase motif and profiled phosphosite gave an understanding of the functional importance of individual phosphosite assayed. Finally, biochemical assays were employed to provide a view towards how different peptide libraries correlate with kinase activity level.…”
Section: Perspectivementioning
confidence: 99%